Handbook of plasticizers - Wypych, George (ChemTec Publishing, 2017)
Handbook of Plasticizers, Third Edition, is an essential professional reference, providing information that enables R & D scientists, production chemists, and engineers the information they need to use plasticizers more effectively, and to avoid certain plasticizers in applications where they may cause health or material durability problems. Plasticizers are vital to the plastics industry, particularly in improving the properties of materials such as PVC. Plasticizers are commonly added to complex mixtures containing a variety of materials, so successful incorporation requires a broad understanding of the mechanisms of plasticizer action, and compatibility with different materials and blends. There is a large selection of commercial plasticizers, and various environmental issues which impact on selection decisions. The book discusses new and historical approaches to the use of plasticizers, explaining mechanisms of plasticizers' action and their behavior in plasticized systems. It goes into detail on the use of plasticizers in a range of specific polymers, polymer blends, and other industrial products. This includes coverage of the impact of plasticizers on processing. George Wypych provides the data and know-how from the most recent sources and updated information required by engineers and scientists working in the plastics industry and the many industry sectors that use plastics in their products. The book covers the uses, advantages, and disadvantages of plasticizers, historical and theoretical background, their effects on process conditions, and health, safety, and environmental issues.